The effect of rubber prices on income and spending pattern among rubber tapper: A case study of rubber tappers in Kuala Krai, Kelantan / Yusnani Mohd Yusoff - Mohd Yusoff, Yusnani (2006)
At the time request of fulfilling the requirement to quality for BBA with honors in finance, a research study titled “The effect of rubber prices on the income and spending pattern of rubber tapper at Kuala Krai” was successfully done. This research contains five chapters, that are Introduction, Literature Review, Research Methodology, Findings and Analysis and the final chapter is Conclusion and Recommendation. The dependent variable to the study is the price of rubber in Malaysia and the independent variables are income and spending pattern among rubber tapper in Kuala Krai focusing on family needs, physiological needs and safety needs. Firstly, this study is conducted with the objectives to ascertain whether as the rubber price increases, the income level and spending pattern will also increase. The findings suggest that all the dependent variables have the relationship with the independent variable. The researcher also pointed out several recommendations, with aims to help the rubber tappers manage their incomes and spending wisely